2022
DOI: 10.1177/17562872221078773
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of early scoring predictors for expedited care in patients with emphysematous pyelonephritis

Abstract: Introduction: Emphysematous pyelonephritis (EPN), an acute necrotizing infection of the kidney and surrounding tissues, is associated with considerable mortality. We evaluated how existing critical care scoring systems could predict the need for intensive care unit (ICU) management for these patients. We also analyzed if CT-imaging further enhances these predictive systems. Patients and Methods: A retrospective analysis of 90 consecutive patients diagnosed clinico-radiologically with EPN from January 2011 to S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…Chawla et al reviewed 90 EPN patients and found that NEWS score was the best at predicting the need for ICU admission. Like in our study, the author found that NEWS score ≥ 5 was the best predictor of the need for urgent admission to the ICU [ 22 ]. In terms of predicting EPN mortality, Krishnamoorthy et al prospectively reviewed 131 EPN patients in 2019 and proposed a prognostic scoring system to predict mortality including 18 parameters [ 23 ].…”
Section: Discussionsupporting
confidence: 73%
“…Chawla et al reviewed 90 EPN patients and found that NEWS score was the best at predicting the need for ICU admission. Like in our study, the author found that NEWS score ≥ 5 was the best predictor of the need for urgent admission to the ICU [ 22 ]. In terms of predicting EPN mortality, Krishnamoorthy et al prospectively reviewed 131 EPN patients in 2019 and proposed a prognostic scoring system to predict mortality including 18 parameters [ 23 ].…”
Section: Discussionsupporting
confidence: 73%
“…According to this classification system, the case in question is categorized as Class IV. In this system, Class IV corresponds to “Class 4 – Bilateral EPN or EPN in a solitary kidney [ 16 ]”.…”
Section: Discussionmentioning
confidence: 99%
“…Not only the risk factors but also the scoring systems should be taken into consideration when deciding the most suitable treatment. In the literature review, Chawla et al analyzed 90 consecutive patients and found that the NEWS scoring system was best able to predict the requirement of ICU care [24]. Krishnamoorthy et al described that the objective and qualitative risk stratification assessment is necessary for treating patients with EPN [25].…”
Section: Discussionmentioning
confidence: 99%